(untitled) (Fiep Bulletin - online, 2015)
Introduction: Aerobic exercise causes different responses in the cardiovascular system. Objective: To evaluate the blood pressure responses of normotensive young subjects underwent a workout performed on a stationary bicycle. Methodology: experimental, and randomized study conducted in LAFEX, conducted with 50 young individuals of both sexes, and were divided into 2 groups (Pbike; Pcontrol), 25 subjects for each group. For realization of Pbike, an stationary bike exercise Movement brand, R7 model was used. Individuals in the experimental protocol were evaluated by intensity of 65% HR reserve, while Pcontrole was at rest. BP was measured at the moments: pre-exercise, immediately after (T / 0), 15 minutes (T / 15), 30 minutes (T / 30) and 45 minutes after exercise completion (T / 45). For BP measurement, was used a semi-automatic machine, brand ONROM 705 IT . For statistical analysis SPSS software (version 20.0) was used. The assessment of data normality is given by the Kolmogorov-Smirnov test. For intergroup and intragroup analysis, the T-Student test, with p <0.05 was applied. Results: In protocol Pbike increased SBP after exercise, except at T / 15 and T / 45, while the PC was no significant change after the session compared to pre. The DAP had significantly increased in the experimental group, both at the time immediately after exercise. In PC increased significantly only when T / 45. Conclusion: The increase of BP in individuals tested were not of great magnitude cardiovascular ensuring the completion of the exercise even with postexercise decrease.